JAK inhibition decreases the autoimmune burden in Down syndrome - Rachubinski, Angela L; Wallace, Elizabeth; Gurnee, Emily; Enriquez-Estrada, Belinda A; Worek, Kayleigh R; Smith, Keith P; Araya, Paula; Waugh, Katherine A; Granrath, Ross E; Britton, Eleanor; Lyford, Hannah R; Donovan, Micah G; et al. (eLife, 2024)
Background:. Individuals with Down syndrome (DS), the genetic condition caused by trisomy 21 (T21), display clear signs of immune dysregulation, including high rates of autoimmunity and severe complications from infections. Although it is well established that T21 causes increased interferon responses and JAK/STAT signaling, elevated autoantibodies, global immune remodeling, and hypercytokinemia, the interplay between these processes, the clinical manifestations of DS, and potential therapeutic interventions remain ill defined. Methods:. We report a comprehensive analysis of immune dysregulation at the clinical, cellular, and molecular level in hundreds of individuals with DS, including autoantibody profiling, cytokine analysis, and deep immune mapping. We also report the interim analysis of a Phase II clinical trial investigating the safety and efficacy of the JAK inhibitor tofacitinib through multiple clinical and molecular endpoints. Results:. We demonstrate multi-organ autoimmunity of pediatric onset concurrent with unexpected autoantibody-phenotype associations in DS. Importantly, constitutive immune remodeling and hypercytokinemia occur from an early age prior to autoimmune diagnoses or autoantibody production. Analysis of the first 10 participants to complete 16 weeks of tofacitinib treatment shows a good safety profile and no serious adverse events. Treatment reduced skin pathology in alopecia areata, psoriasis, and atopic dermatitis, while decreasing interferon scores, cytokine scores, and levels of pathogenic autoantibodies without overt immune suppression. Conclusions:. JAK inhibition is a valid strategy to treat autoimmune conditions in DS. Additional research is needed to define the effects of JAK inhibition on the broader developmental and clinical hallmarks of DS. Funding:. NIAMS, Global Down Syndrome Foundation. Clinical trial number:. NCT04246372.
Keywords: down syndrome; autoimmunity; JAK; skin; inflammation; interferons